Artemisia annua L.- Vernonia amygdalina Del: A Potential Herbal Artemisinin Combination Treatment against Malaria - Nambejja, Cissy; Ogwang, Patrick; Engeu Onegi, Berna; Anyama, Norbert; Matu, Esther (Journal of Pharmaceutical Research International, 2016)
The aim of the study was to determine the potential of Vernonia amygdalina - Artemisia annua combination as a possible herbal artemisinin combination treatment of malaria. Place and Duration of Study: Study was conducted at Natural Chemotherapeutics Research Institute, Ministry of Health, Kampala Uganda and at the Centre for Traditional Medicine and Drug Methodology: After authentication of the plants, mature healthy Artemisia annua and Vernonia amygdalina leaves were collected and shade dried over 2 weeks. The dry materials were then each separately extracted by maceration using Petroleum ether and methanol. The filtrates obtained were first concentrated by fanning and then oven dried at 50°C to constant weight of dry extract. Eight groups of Plasmodium berghei ANKA infected mice were treated once daily for 4 days from the day of inoculation as follows; group I, 200 mg/kg bwt of A. annua methanol extract; group II, 125 mg/kg of V. amygdalina methanol extract; group III, 200 mg/kg of A. annua pet ether extract; group IV, 125 mg/kg of V. amgydalina pet ether extract; group V, 125 mg/kg of V. amygdalina + 200 mg/kg of A. annua methanol extracts group; VI, 125 mg/kg of V. amygdalina + 200 mg/kg of A. annua pet ether extracts; group VII (positive control), 15 mg/kg of artemisinin+ 3mg/kg of naphthoquine and group VIII (negative control), 0.2 ml 10% Tween 80. Parasitaemia in each mice was determined by microscopy on day 5 while survival times were recorded over 30 day period. The means of percent parasitaemia and survival times for each treatment group were determined and differences tested for significances using One-way analysis of variance followed by Student's t-test at P=0.05 using STATA version 13.0 statistical program. Results: The petroleum ether extracts combination produced 100% parasite clearance by day 5 just like the Artemisinin-Napthoquine. The survival times for the herbal combination were however poor and significantly less i.e 10.67±1.09 days compared to more than 30.0 ± 0.0 days for the ACT, P=0.000. Conclusion: The V. amygdalina-A. annua petroleum ether extract combination shows promise for use as a herbal artemisinin combination against malaria however the survival times need improvement to match that of the ACT.
Keywords: Artemisia annua; Vernonia amygadalina; herbal-combination; malaria